2020
DOI: 10.1186/s12889-020-09283-3
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in children and adolescents with psychiatric disorders

Abstract: Background: Unintentional injuries are a leading cause of morbidity and mortality in children of all ages. Prevention strategies require knowledge of risk factors, and behavior and psychiatric disorders have been suggested to influence the risk of injury during childhood. While externalizing disorders have been found to increase the risk for injuries, results are mixed regarding internalizing disorders, such as affective and anxiety conditions, and Autism Spectrum Disorders (ASD). There is a need for large sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 44 publications
(60 reference statements)
1
24
0
Order By: Relevance
“…A total of 36 results were retrieved from the 31 studies. 9 , 16 , 17 , 18 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 Twenty-nine of the 36 results showed a significant association between ASD and self-harm, 9 , 18 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 63 , 64 , 66 , 67 , 68 , 69 , 70 , 71 , 72 and people with ASD were at similarly increased risk of both self-injurious behavior and suicidality. Included studies were published from 1999 to 2021.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 36 results were retrieved from the 31 studies. 9 , 16 , 17 , 18 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 Twenty-nine of the 36 results showed a significant association between ASD and self-harm, 9 , 18 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 63 , 64 , 66 , 67 , 68 , 69 , 70 , 71 , 72 and people with ASD were at similarly increased risk of both self-injurious behavior and suicidality. Included studies were published from 1999 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 31 studies, 6 (19%) recruited participants in a clinical setting 9 , 53 , 59 , 65 , 71 , 72 and 25 (81%) recruited participants in a nonclinical setting 16 , 17 , 18 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 70 (eFigure 1 in the Supplement ). Most studies (n = 22 [71%]) used the general population without ASD as the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no national reference data on traumatic events in children, but a recent study of a large population-based cohort of Swedish children and adolescents demonstrated a general pattern of increased risk for concurrent injuries with most psychiatric diagnoses. 23 Early identification of physical child abuse by healthcare professionals is essential to prevent further maltreatment and in the worstcase scenario, death. According to King et.…”
Section: Discussionmentioning
confidence: 99%